Kesehatan Spritual Terapi Al-Qur'an sebagai Pengobatan Fisik dan Psikologis di Masa Pandemi COVID-19 - Rosyanti, Lilin; Hadi, Indriono; Akhmad, Akhmad (Poltekkes Kemenkes Kendari, 2022)
Improving public health both physically and psychologically requires a spiritual-based therapeutic approach that is easy, cheap, practical and efficient, one of which is the spiritual therapy of the Qur'an, especially in the face of the COVID-19 pandemic. The holistic nursing perspective makes the nursing profession view a person as a complete biopsychosocial being physically, mentally, socially, and spiritually who are interrelated and influence one another. This literature review aims to provide an overview of scientific studies on the effects and benefits of the spiritual health of Al-Qur'an therapy as physical and psychological treatment in improving public health during the COVID-19 pandemic. Methodology of literature review by searching biomedical databases on Medline, Embase, PsychINFO, Scopus, Pubmed, and Google Scholar, all research articles and literature reviews were included as search criteria. Data were collected and concluded as a review of scientific narrative writing. There are several categories of results consisting of: description of spiritual health, spiritual health in an Islamic perspective, therapy of the Qur'an, the holy verses of the Qur'an as a healing medicine, physiology of sound therapy of the Qur'an on the hearing system. and brain. The benefits and therapeutic effects of the Qur'an can increase endorphins in the brain, changes in TTV and body physiology, improves autism disorders and stroke disorders, changes in memory, changes in brain waves, changes in physiological responses in the PICU and ICU rooms, reduces anxiety. Spiritual health with Al-Qur'an therapy is the main and important solution in helping to heal physical, mental, spiritual illnesses, and improving public health in facing the challenges of the COVID-19 pandemic.